2006
DOI: 10.1016/j.ejphar.2006.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic actions of the anti-diabetic drug metformin on osteoblasts in culture

Abstract: An association has been previously established between uncompensated diabetes mellitus and the loss of bone mineral density and/or quality. In this study, we evaluated the effects of metformin on the growth and differentiation of osteoblasts in culture. Treatment of two osteoblast-like cells (UMR106 and MC3T3E1) with metformin (25-500 microM) for 24 h led to a dose-dependent increase of cell proliferation. Metformin also promoted osteoblastic differentiation: it increased type-I collagen production in both cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
162
3
24

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(209 citation statements)
references
References 59 publications
20
162
3
24
Order By: Relevance
“…In contrast, metformin induces an osteogenic effect in vivo and in vitro, possibly mediated via RUNX2 and activation of AMPK (Cortizo et al 2006, Gao et al 2010, Molinuevo et al 2010, Zhen et al 2010. Co-treatment of BMPC with metformin partially inhibits the adipogenic action of rosiglitazone (Molinuevo et al 2010).…”
Section: Ampk and The Skeletal Effects Of Antidiabetic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, metformin induces an osteogenic effect in vivo and in vitro, possibly mediated via RUNX2 and activation of AMPK (Cortizo et al 2006, Gao et al 2010, Molinuevo et al 2010, Zhen et al 2010. Co-treatment of BMPC with metformin partially inhibits the adipogenic action of rosiglitazone (Molinuevo et al 2010).…”
Section: Ampk and The Skeletal Effects Of Antidiabetic Drugsmentioning
confidence: 99%
“…It was shown that AICAR and metformin both cause a direct osteogenic effect in MC3T3-E1 cells (Cortizo et al 2006, Kanazawa et al 2007, Jang et al 2011. These actions include a dose-dependent increase in cell proliferation, type I collagen production, alkaline phosphatase (ALP) activity, and mineral deposition.…”
Section: Effect Of Ampk Activation On Bone Cell Activities In Vitro Amentioning
confidence: 99%
“…Several studies have indeed shown that TZDs increase fracture risk (10,11). In contrast, metformin, another widely prescribed anti-diabetic drug (12), is osteogenic in vitro (13,14) and reduces the risk of fracture in DM patients (15), as well as inhibiting the bone loss induced by ovariectomy (OVX) in rats (16,17). However, our recent studies showed no beneficial effect of metformin on bone mass and fracture healing in rodents (18).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others reported that metformin (1 mM) had no effect on the osteogenic differentiation of MSCs when cultured in β-glycerol phosphate and ascorbic2-phosphate medium (Wu et al 2011). Cortizo et al (2006) also found that metformin had no effect on ALP activity in UMR106 rat osteosarcoma cells. At the concentration of 2 mM, metformin reduced mineralization of osteoblasts (Kasai et al 2009).…”
Section: Discussionmentioning
confidence: 82%
“…Molinuevo et al (2010) found that 10 μM metformin can increase ALP activity and mineralization in rat BM progenitor cells. Cortizo et al (2006) showed that metformin (25-100 μM) can increase type I collagen production and ALP activity in MC3T3E1 cells. Moreover, metformin can reverse rosiglitazoneinduced bone loss in rats (Sedlinsky et al 2011).…”
Section: Discussionmentioning
confidence: 99%